Manajemen Dakwah LDII dalam Pemberdayaan Ekonomi Jamaah: Perspektif Sustainable Development Goals (SDGs) - Nadia Cahaya Amanda; Rohman (Jurnal Manajemen Dakwah, 2026)
This study examines dakwah management in empowering congregational economy with a focus on Lembaga Dakwah Islam Indonesia (LDII) within the perspective of the Sustainable Development Goals (SDGs). LDII was chosen as the research object because it has concrete programs that integrate dakwah with community economic development, such as productive zakat, productive waqf, and sharia cooperatives. The research method employed observation, interviews, and documentation to explore the dakwah management practices implemented by LDII. The findings reveal that LDII successfully applies the management functions (planning, organizing, actuating, and controlling) systematically, ensuring that economic empowerment programs for the congregation run effectively and sustainably. Empirical evidence highlights LDII’s contribution to achieving SDGs, particularly Goal 1 (No Poverty), Goal 8 (Decent Work and Economic Growth), and Goal 10 (Reduced Inequalities). This study provides practical implications for other dakwah institutions to develop strategies based on community economic empowerment, while also strengthening academic contributions to the study of dakwah management and sustainable development.